The nonlinear impact of digital finance on carbon emission efficiency: evidence from Chinese cities - Chen, Yanling (Frontiers in Environmental Science, 2026)
Amid persistent growth in global carbon outputs, enhancing carbon emission efficiency (CEE) has emerged as a pivotal strategy for synchronizing economic and ecological objectives. Digital finance (DF), leveraging its distinctive technological capabilities and inclusive financial features, plays a catalytic role in CEE optimization. This research methodically investigates the effect of DF on CEE using panel data (282 Chinese cities, 2011–2022) and several panel econometric estimation techniques. The findings reveal that: 1. The influence of DF on CEE follows a U-shaped trend, first suppressing and then promoting. Heterogeneity analysis reveals that the U-shaped relationship is more pronounced across two dimensions—coverage breadth and usage depth—as well as in resource-based cities and key environmental protection cities. 2. Mechanism analysis demonstrates that DF exerts a U-shaped effect on green technology innovation, human capital accumulation, and public environmental awareness, thereby indirectly shaping CEE. 3. Policy synergy test reveals that the “Carbon Emission Trading” and “Low-Carbon City” pilot policies significantly amplify the U-shaped relationship between DF and CEE. In contrast, the effect of digitalization and infrastructure-oriented policies, exemplified by the “Smart City” and “Broadband China” pilot policies, is statistically insignificant. This study not only enriches the theoretical understanding of DF’s environmental effects but also provides policy insights for leveraging DF to accelerate green transformation.